SEPARATION OF MITOCHONDRIAL MEMBRANES OF NEUROSPORA CRASSA : II. Submitochondrial Localization of the Isoleucine-Valine Biosynthetic Pathway - Cassady, W. E. (The Rockefeller University Press, 1972)
Separation of Neurospora mitochondrial outer membranes from the inner membrane/matrix fraction was effected by digitonin treatment and discontinuous density gradient centrifugation. The solubilization of four isoleucine-valine biosynthetic enzymes was studied as a function of digitonin concentration and time of incubation in the detergent. The kinetics of the appearance of valine biosynthetic function in fractions outside of the inner membrane/matrix fraction, coupled with enzyme solubilization patterns similar to that for the matrix marker, mitochondrial malate dehydrogenase, indicate that the four isoleucine-valine pathway enzymes are localized in the mitochondrial matrix.